2015
DOI: 10.1111/ijpo.12064
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep stages and hunger scores in 36 children

Abstract: These findings suggest that delayed bedtime, which increases the proportion of REM sleep and decreases the proportion of SWS, results in higher hunger levels in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…In addition, sleep architecture may also play a role in weight regulation, as a recent study demonstrated significant associations among total rapid eye movement sleep, slow wave sleep and hunger scores in children. (25) Reliance on parent report sleep duration is a primary limitation of this study, although consistent with prior studies on the association. It should be noted that almost all prior studies have relied on parent report, rather than objective actigraphy, to assess sleep schedule characteristics, and this may (29); the authors speculated that diminished sleep quality and altered sleep architecture may be linked to metabolic and neurophysiological changes that are obesogenic.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, sleep architecture may also play a role in weight regulation, as a recent study demonstrated significant associations among total rapid eye movement sleep, slow wave sleep and hunger scores in children. (25) Reliance on parent report sleep duration is a primary limitation of this study, although consistent with prior studies on the association. It should be noted that almost all prior studies have relied on parent report, rather than objective actigraphy, to assess sleep schedule characteristics, and this may (29); the authors speculated that diminished sleep quality and altered sleep architecture may be linked to metabolic and neurophysiological changes that are obesogenic.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the link between social jet lag and obesity may not be present until later childhood for most individuals. In addition, sleep architecture may also play a role in weight regulation, as a recent study demonstrated significant associations among total rapid eye movement sleep, slow wave sleep and hunger scores in children …”
Section: Discussionmentioning
confidence: 99%
“…Sleep timing behavior is also associated with excess weight and poor eating habits in pediatric samples. For instance, children with a delayed bedtime and increased REM sleep measured through PSG reported higher hunger scores the following morning [16]. In a nationally representative sample, parental report of children (3–12y) who slept less or went to bed later at baseline assessment had higher BMIs and were more likely to be overweight at their 5-year follow-up compared to children who slept more than 11 hours a night [17].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates such as sucrose, fructose, and glucose are known substrates for Streptococci mutans, and the intricate mechanism between sleep, salivary glucose, and caries should be explored further. Shorter sleep duration or delayed bedtime is also associated with reduced self-regulation of appetite in children and may be related to over-eating behaviours (Burt et al 2014;Arun et al 2016;Miller et al 2019). This consideration might have significant importance for caregivers, healthcare providers, and future researchers because ad libitum bottle feeding and breastfeeding by mothers to get their children to sleep is a proven risk factor for ECC (Avila et al 2015;Feldens et al 2018).…”
Section: Discussionmentioning
confidence: 99%